Hubungan Gangguan Kognitif dengan Kemandirian Lansia dalam Melakukan Basic Activity of Daily Living (BADL) - Ni Made Riasmini; Luthfiyah Astried; Yeti Resnayati (Poltekkes Kemenkes Padang, 2025)
Cognitive impairment experienced by the elderly is a serious problem because it has an impact on the ability of the elderly to carry out daily activities. After old age, there are a number of potential physical changes in a person. This is related to differences in the speed of cognitive function in the elderly because it can interfere with the independence of the elderly to carry out Basic daily activities. The aim of this research is determine the relationship between cognitive impairment and elderly independence in carrying out Basic Activities Daily Living (BADL).the elderly. This type of research is quantitative with a cross-sectional approach. The population of this study was 292 people with a sample of 68 respondents and sampling using simple random sampling techniques. The results of data analysis with the chi-square test showed that there is a meaningful relationship between cognitive impairment and independence of Basic Activity Daily Living (BADL) with p-value<0.001. The conclusion is the elderly with severe cognitive impairment are at greater risk of experiencing dependency in BADL compared to elderly people who experience mild cognitive impairment.